Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/nchembio.302
|View full text |Cite
|
Sign up to set email alerts
|

Domino access to highly substituted chromans and isochromans from carbohydrates

Abstract: Herein we describe the synthesis of highly substituted chromans and isochromans using carbohydrates as starting materials. Our approach makes use of a Pd-catalyzed domino reaction consisting of oxidative addition, followed by two carbopalladation steps and completed by a cyclization to annelate the benzene moiety. The versatility of this route has been demonstrated by a small library of highly substituted chromans and isochromans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…After having established several methods of domino carbopalladation reactions which employ dialkynyl-substituted bromoglycals [1720] or bromoarenes [21], we envisioned to apply a similar procedure for the preparation of anthracycline derivatives. Therefore, the D-ring was exchanged for a pyranose, as described in our previous synthetic approaches for the syntheses of chromans, isochromans and biphenyls, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After having established several methods of domino carbopalladation reactions which employ dialkynyl-substituted bromoglycals [1720] or bromoarenes [21], we envisioned to apply a similar procedure for the preparation of anthracycline derivatives. Therefore, the D-ring was exchanged for a pyranose, as described in our previous synthetic approaches for the syntheses of chromans, isochromans and biphenyls, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the D-ring was exchanged for a pyranose, as described in our previous synthetic approaches for the syntheses of chromans, isochromans and biphenyls, respectively. These 2-bromoglycals 15 are well-known compounds and their synthesis was accomplished according to literature-known procedures [1718]. The dialkyne unit provides both the A-ring and the information for the formation of the B and C-ring within the palladium-catalyzed domino transformation [2227].…”
Section: Resultsmentioning
confidence: 99%
“…Our recent interest in domino reactions starting with 2-brominated glycals [2628] motivated us to investigate also the behaviour of peracetylated 2-bromogalactal 10 in Sonogashira–Hagihara reactions (Table 2). We found that 10 is much less reactive than 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Using a Pd-catalyzed domino reaction under microwave irradiation, Werz and coworkers prepared a library of chromans and isochromans from bromoglycal as a starting material (Leibeling et al 2010). This study opens doors for the generation of highly functionalized scaffolds for libraries from carbohydrates in high-throughput synthesis.…”
Section: Automated Carbohydrate Synthesismentioning
confidence: 98%